Bach1 Induces Endothelial Cell Apoptosis and Cell-Cycle Arrest through ROS Generation - Wang, Xinhong (Oxid Med Cell Longev, 2016)
The transcription factor BTB and CNC homology 1 (Bach1) regulates genes involved in the oxidative stress response and cell-cycle progression. We have recently shown that Bach1 impairs cell proliferation and promotes apoptosis in cultured endothelial cells (ECs), but the underlying mechanisms are largely uncharacterized. Here we demonstrate that Bach1 upregulation impaired the blood flow recovery from hindlimb ischemia and this effect was accompanied both by increases in reactive oxygen species (ROS) and cleaved caspase 3 levels and by declines in the expression of cyclin D1 in the injured tissues. We found that Bach1 overexpression induced mitochondrial ROS production and caspase 3-dependent apoptosis and its depletion attenuated H(2)O(2)-induced apoptosis in cultured human microvascular endothelial cells (HMVECs). Bach1-induced apoptosis was largely abolished when the cells were cultured with N-acetyl-l-cysteine (NAC), a ROS scavenger. Exogenous expression of Bach1 inhibited the cell proliferation and the expression of cyclin D1, induced an S-phase arrest, and increased the expression of cyclin E2, which were partially blocked by NAC. Taken together, our results suggest that Bach1 suppresses cell proliferation and induces cell-cycle arrest and apoptosis by increasing mitochondrial ROS production, suggesting that Bach1 may be a promising treatment target for the treatment of vascular diseases.